Aluminum doped ZnO transparent conducting thin films prepared by sol-gel dip coating technique for solar cells and optoelectronic applications. (12th May 2018) - Balaprakash, V.; Gowrisankar, P.; Sudha, S.; Rajkumar, R.
Abstract: Aluminium-doped ZnO (AZO) nanostructured transparent conducting thin films have been deposited on a glass substrate through sol-gel dip coating process by alterable aluminium substance of 0–5 at.%. Structural, morphological, electrical and optical properties of the composed films investigated employing X-ray diffraction (XRD), scanning electron microscopy (SEM), four-probe conductive measurement strategy and UV–visible Spectroscopy (UV–vis), respectively. The high intensity razor-sharp (002) peak observed in 1 at.% doped film annealed at 450 °C. The 0.5 at.% doped film reveals porous nanostructure and spherical crystalline size is relatively 38nm. The electrical resistivity of 3.2 × 10 –2 Ωcm is obtained in 1 at.% doped film annealed at 450 °C. Compared to all, 0.5 at.% doped film produces over 90% transmittance. The obtained optical band gap energies are ranging from 3.34 eV to 3.62 eV. Preparatory outcomes anticipated in these investigation exhibit AZO films are being valuable as guaranteeing transparent conductive oxide (TCO) for solar cells and other optoelectronic device applications.